2021
DOI: 10.3389/fvets.2021.615029
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Mycobacterium avium Subspecies paratuberculosis (MAP) Microorganisms Using Antigenic MAP Cell Envelope Proteins

Abstract: Cell envelope proteins from Mycobacterium avium subspecies paratuberculosis (MAP) that are antigenically distinct from closely related mycobacterial species are potentially useful for Johne's Disease (JD) diagnosis. We evaluated the potential of ELISAs, based on six antigenically distinct recombinant MAP cell envelope proteins (SdhA, FadE25_2, FadE3_2, Mkl, DesA2, and hypothetical protein MAP1233) as well as an extract of MAP total cell envelope proteins, to detect antibodies against MAP in the sera of infecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 55 publications
(33 reference statements)
0
10
0
Order By: Relevance
“…As a result, they perform poorly between the initial CMI response and the sub (clinical) stages of infection [ 22 ]. The application of omic approaches have suggested that they could be a potential source of new biomarkers with sensitivity and specificity values reported ranging between 82 and 94% [ 11 , 12 ]. However, no omic study has assessed MAP infection associated changes in youngstock.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As a result, they perform poorly between the initial CMI response and the sub (clinical) stages of infection [ 22 ]. The application of omic approaches have suggested that they could be a potential source of new biomarkers with sensitivity and specificity values reported ranging between 82 and 94% [ 11 , 12 ]. However, no omic study has assessed MAP infection associated changes in youngstock.…”
Section: Discussionmentioning
confidence: 99%
“…These studies suggest that the performance of these omic study-derived biomarkers exceeds many commercially available tests [ 8 ]. This stated, these have focused on post-partum cattle [ 12 , 13 ] so that the application of these biomarkers in youngstock is questionable.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We also found some animals with substantial IT reaction and low antibody values according to OD, with loss of sensitivity to the ELISA test, which could have been because they were in the early stages of the disease [ 7 ]. Nevertheless, sensitivity deficiencies to the ELISA test related to the antigens used in the tests have also been observed, in addition to the variation of sensitivity according to the country when the animals were infected by different strains [ 28 ].…”
Section: Discussionmentioning
confidence: 99%